Accelerometer Output and MET Values of Common Physical Activities - Kozey, Sarah L. (2010)
PURPOSE: This paper 1) provides the calibration procedures and methods for metabolic and activity monitor data collection, 2) compares measured MET values to the MET values from the Compendium of Physical Activities, and 3) examines the relationship between accelerometer output and METs for a range of physical activities METHODS: Participants (n=277) completed 11 activities for seven minutes each from a menu of 23 physical activities. Oxygen consumption (VO(2)) was measured using a portable metabolic system and an accelerometer was worn. MET values were defined as follows; measuredMETs (VO(2)/measured RMR) and standardMETs (VO(2)/3.5ml·kg·min(−1)). For the total sample and by sub-group (age [young <40y], sex and BMI [normal-weight <25 kg·m(2)]), measuredMETs and standardMETs were compared to the Compendium, using 95% confidence intervals to determine statistical significance (α=0.05). Average count·min(−1) for each activity and the linear association between count·min(−1) and METs are presented. RESULTS: Compendium METs were different than measured METs for 17/21 activities (81%). The number of activities different than the Compendium were similar between sub-groups or when standard METs were used. The average counts for the activities ranged from 11 counts·min(−1)(dishes) to 7490 counts·min(−1) (2.23m·s(−1), 3%) The r(2) between counts and METs was 0.65. CONCLUSIONS: This study provides valuable information about data collection, metabolic responses, and accelerometer output for common physical activities in a diverse participant sample. The Compendium should be updated with additional empirical data and linear regression models are inappropriate for accurately predicting METs from accelerometer output.